Alokasi Biaya Bersama untuk Produk Bersama dalam Penentuan Harga Jual - Umi Nadhiroh; Srikalimah Srikalimah (SEIKO : Journal of Management & Business, 2021)
The study of purpose is to analyze the allocation of joint costs in determining the selling price of products at UD. Konto Mulyo. The method used in this research is descriptive method, in this case, it is done by collecting related costs, then grouping them into raw material costs, labor costs and factory overhead costs to determine the cost of goods manufactured and the selling price according to the existing theory. According to the results of the analysis that has been done, there are different results between the methods used by UD. Konto Mulyo with the method used by the researcher. The results obtained show that the cost of goods manufactured for each product is much lower than the selling price set by the company. The calculations made by the company produce a higher cost of goods sold than the results of the analysis, so that the gross profit from the calculation of the company is smaller than the gross profit calculation from the analysis results. The results of the calculation of the selling price obtained by UD. Konto Mulya for each product, namely: Paving Block of Rp. 6,000, - Pillar Rp. 150,000, - Batako Rp. 12,000, - The winds Rp. 15,000, - Sewer Rp. 90,000, - and the calculation of the research results, namely: Paving Block of Rp. 4,939, - Pillar Rp. 109,098, - Batako Rp. 9,208, - Winds Rp. 11,789, - Culvert Rp. 65,431, -. So there is a price difference between those at UD. Konto Mulyo with the results of the researchers' calculations. Thus, the analysis of joint cost allocation using the relative sale value method in this study is appropriate and appropriate. Keywords: Cost of production; full coting; joint cost.